The Design of Integrated Tapioca Agro-Industries Development Model - Azmi Alvian Gabriel; Susinggih Wijana; Sri Kumalaningsih (Graduate Program, 2014)
Tapioca is an agro-industries product with high consumption level that reached 1.132 million tons per year. However, that potential was not balanced with the productivity levels of tapioca industries due to weak capacity and production period. This research aims to design the development model of tapioca agro-industries which can produce in a sustainable way in terms of quality as well as quantity of product. Study of research location was in the Kaur Regency of Bengkulu Province. This research consists of three stages. The first study was conducted to know the projection of the raw materials availability and product demand using regression and quadratic equation smallest method. The result of calculation projections showed the availability of raw cassava achieved an average of 10 million tons per year and the demand for tapioca 1.36 million tons per year. The second study was done to determine the partnership patterns between company and farmers using pairwise comparison and rating scale methods. From the results of the research note that